2009
DOI: 10.1002/mnfr.200800021
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between antiangiogenic activity and antioxidant activity of various components from propolis

Abstract: Propolis possesses various physiological activities. In this study, we examined the antiangiogenic and antioxidant activities of various components from propolis: acacetin, apigenin, artepillin C, caffeic acid phenethyl ester, chrysin, p-coumaric acid, galangin, kaempferol, pinocembrin, and quercetin. The effects of these components were tested on in vitro models of angiogenesis, tube formation and growth of human umbilical vein endothelial cells (HUVECs). Furthermore, these components were evaluated for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 51 publications
(55 reference statements)
6
95
0
2
Order By: Relevance
“…Banskota et al (2001aBanskota et al ( , 2001b reported that the antioxidative activity of propolis is due to its phenolic components, which also possess antitumor and antihepatotoxic activities. In our previous report, we also found a correlation between antioxidant activity and antiangiogenic activity in various components from propolis (Ahn et al, 2009). The components from propolis such as kampferol (g), phenethyl caffeate (n), galangin (o) and quercetin not only had strong antioxidant activity but also antiangiogenic activity.…”
Section: Effect Of Propolis On Frap Assaymentioning
confidence: 51%
See 1 more Smart Citation
“…Banskota et al (2001aBanskota et al ( , 2001b reported that the antioxidative activity of propolis is due to its phenolic components, which also possess antitumor and antihepatotoxic activities. In our previous report, we also found a correlation between antioxidant activity and antiangiogenic activity in various components from propolis (Ahn et al, 2009). The components from propolis such as kampferol (g), phenethyl caffeate (n), galangin (o) and quercetin not only had strong antioxidant activity but also antiangiogenic activity.…”
Section: Effect Of Propolis On Frap Assaymentioning
confidence: 51%
“…Furthermore, these EEP samples contained a large amount of antioxidative compounds, such as caffeic acid (a), kaempferol (g), galangin (o) and cinnamyl caffeate (p). We previously reported that phenolics such as caffeic acid (a), kaempferol (g), phenethyl caffeate (n), galangin (o) and cinnamyl caffeate (p) exhibited strong radical-scavenging activity (Ahn et al, 2009;Kumazawa et al, 2004). On the other hand, constituents of propolis from Aewol (P17) and Pyoseon (P18) were apparently different from those from other regions and contain a few compounds shown in Fig.…”
Section: Effect Of Propolis On Frap Assaymentioning
confidence: 97%
“…Many investigations tended to address its anticancer activity (Vatansever et al, 2010;Eom et al, 2010;Sawicka et al, 2012). Propolis can be utilized as therapeutic medications for the human diseases such as tumors because it has many components that revealed antiangiogenic and antioxidant actions (Ahn et al, 2009). Sforcin, (2007 explore that propolis could affect antibody production; macrophage activation and lymphocyte proliferation.…”
Section: Modulator Impacts Of Propolis Extract Against Doxorubicin Mementioning
confidence: 99%
“…Currently, there are papers published on the in vitro antioxidant activity of flavonoids and a correlation between the antioxidant capacity and chemical structure (Wolfe and Liu, 2008). Ahn et al (2009) found that the anti-angiogenic action of various components of propolis, such as caffeic acid phenyl ester, kaempferol, and quercetin, is correlated with antioxidant capacity of the same (Ahn, et al, 2009). That way, extracts of E. Suberosum could be useful in the treatment and even prevention of diseases related to oxidative stress.…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 99%